2009
DOI: 10.1107/s0021889809017701
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of small-angle X-ray scattering from thylakoid membranes

Abstract: Small‐angle X‐ray scattering (SAXS) patterns are calculated from a three‐dimensional model of photosynthetic thylakoid membranes. The intricate structure of the thylakoids is represented by sampling random `electron density points' on geometric surfaces. The simulation setup works as a virtual instrument, allowing direct comparison with experimental data. The simulations qualitatively reproduce experimental data and thus clarify the structural origin of the scattering features. This is used to explain recent S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…For model validation purposes we employ the brute-force simulation setup previously used to investigate scattering from photosynthetic membrane systems 17 (see details in Materials and Methods G ). We have simulated up to 6 double bilayer unit cells (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For model validation purposes we employ the brute-force simulation setup previously used to investigate scattering from photosynthetic membrane systems 17 (see details in Materials and Methods G ). We have simulated up to 6 double bilayer unit cells (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The simulations consists of calculating the Debye equationfor a specified N -point cloud with scattering lengths b i and separations r ij representing the sample as described in 17 . The membranes are represented as large discs with a radius of 1000 Å so any effects of the finite disc size is outside the q -range in question.…”
Section: Methodsmentioning
confidence: 99%
“…For reasons probably related to symmetry and/or lack of contrast, the first order Bragg peak of the multilamellar grana stacks is missing -under all experimental conditions tested. (For theoretical treatment of the small angle scattering of granal thylakoid membranes, see [26].) Instead, as will be shown elsewhere, grana, as well as PSII membrane-pairs devoid of the interconnecting stroma thylakoids, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, more sophisticated analyses of scattering data on photosynthetic systems are required. Theoretical calculations of Kirkensgaard et al (2009), based on simulated scattering patterns, suggested a possible route for further modeling which was recently demonstrated to provide a framework for the analysis of the full scattering curve from cyanobacterial membranes (Jakubauskas et al, 2019). The general equation for the scattering intensity of particles in solution is…”
Section: Small Angle Scattering Analysismentioning
confidence: 99%
“…There are currently about 40-50 works published on scattering from photosynthetic systems-photosynthetic bacteria, diatoms and other algae and of course from higher plants. Small-angle scattering has been used to investigate structure and dynamic changes of thylakoid membrane systems of plants (Finean et al, 1953;Kratky et al, 1959;Kreutz and Menke, 1960a;Kreutz and Menke, 1960b;Kreutz and Menke, 1962;Kreutz, 1963a;Kreutz, 1963b;Kreutz, 1964;Sadler, 1976;Li, 1979;Sadler and Worcester, 1982a;Sadler and Worcester, 1982b;Diederichs et al, 1985;Garab et al, 1997;Kirkensgaard et al, 2009;Nagy, 2011;Nagy et al, 2011;Nagy et al, 2013;Ünnep et al, 2014b;Herdean et al, 2016;Ünnep et al, 2017;Zsiros et al, 2020;Ünnep et al, 2020), protists (Sadler et al, 1973;Worcester, 1976;Sadler and Worcester, 1982a), diatoms (Nagy et al, 2011;Nagy et al, 2012), photosynthetic bacteria (Pape et al, 1974;Hodapp and Kreutz, 1980;Liberton et al, 2013b;Ünnep et al, 2014a;Li et al, 2016;Stingaciu et al, 2016;Eyal et al, 2017;Jakubauskas et al, 2019), algae (Nagy et al, 2011;Nagy...…”
Section: Introductionmentioning
confidence: 99%